Assessment of the mobility of mothers post partum and identification of those at greatest risk of venous thromboembolism. (16th November 2010) - Sharma, R; Atkin, H; MacKillop, L; Paterson-Brown, S
Abstract : Objectives: The authors aim to directly assess the mobility of Mothers following delivery and subsequently aim to relate and compare venous thromboembolism (VTE) risk with current guidelines on VTE thromboprophylaxis post partum. Background: VTE still remains the leading cause of direct maternal deaths in the western world and this risk is greatest in the postnatal period. Mode of delivery and postnatal mobility are extremely important contributory factors. Materials and Methods: 200 antenatal women were recruited into the study. Each was given a pedometer (digital step counter) and record sheet for recording the number of steps taken daily for 7-day post partum. Results: 72 women completed the study. The distribution according to delivery mode were as follows; spontaneous vertex delivery (SVD) =21, vaginal instrumental =21, elective Caesarean section (CS) =20, emergency CS =10. Mothers who underwent vaginal instrumental deliveries had the longest labours followed by SVD then emergency CS. However those who underwent any form of vaginal delivery were first mobile. By day 7 post partum, women following vaginal delivery were almost twice as mobile than those who underwent CS. Interestingly, women who underwent emergency CS were more mobile than those who had elective CS. Raised body mass index was an important contributory factor. Summary: There are a number of contributory risk factors for VTE. Assumptions regarding mobility according to delivery mode must not be made. Continous individual risk assessment from preconception to post partum is essential in reducing VTE morbidity and mortality.